Where is organic food produced and consumed? The determinants of the location of organic food production and consumption in the U.S.A. - Holste, Kelsey A. (Kansas State University, 2009)
The objective of this thesis is to determine the factors that impact the location of organic food production and organic food consumption. The models used test to see if organic foods are consumed where they are produced, the characteristics of consumers which influence their organic consumption, and if organic production is located in the same areas as conventional production. The results of this study showed that organic production is not dependent on conventional production. Education was found to be positively correlated to organic production and consumption while income actually had an opposite effect. Organic production and consumption were also linked to the political liberalness of a state. It was found that urban populations had a negative impact on organic production and Whole Foods stores had a positive effect.
Keywords: Organic Production; Organic Consumption; Agriculture, General (0473); Economics, Agricultural (0503)